Meningkatkan Penjualan Produk Umkm Dengan Memanfaatkan Media Sosial Tiktok Dan Aplikasi Canva - Santi Octavia; Ningky Sasanti (Jurnal Abdimas Ekonomi dan Bisnis, 2023)
Technological developments have a significant impact on UMKM players. So, inevitably,UMKM players must adjust to marketing that used to be conventional and switch to online.Online sales are one of the right marketing strategies to use because more and more people areaccessing the internet, one way to market products or sales via the internet is to market throughsocial networks such as Facebook, Twitter, Instagram, tik-tok. The benefits of CommunityDevelopment activities carried out at UMKM - Mutiara Depok Housing are in addition toproviding assistance and socializing product marketing digitally with Tiktok Social-Media inincreasing product sales and expanding market share by utilizing the Canva Application forbranding product photos through digital marketing. Of the 12 UMKM players who participatedin this activity, it shows that 80% of UMKM already have and utilize social media for theirproduct marketing activities. As for those who have not used it because they do not understandits use, especially the Canva application. Keywords: UMKM (Micro, Small, and Medium Enterprises), Social Media Marketing, OnlineMarketing